PENGARUH PEMBELAJARAN KOOPERATIF TIPE GROUP INVESTIGATION BERBASIS EKSPERIMEN INKUIRI TERHADAP MOTIVASI BELAJAR SISWA (UPEJ Unnes Physics Education Journal, 2013)
Zinc Oxide doped Gallium Oxide (Ga2O3:Zn) thin films have been successfully deposited at corning glass and silicon (1 1 1) substrat with a plasma power 20.16 W with substrat temperature 600°C dan 635°C using dc magnetron sputtering method. The crystal structure of films were characterized using XRD (X-ray diffraction). Morphology films ware characterized using SEM (Scanning Electron Microscopic). Optical transmittance characterized by UV-vis spectrometer. Ga2O3:Zn thin films on a substrat temperature of 600°C dan 635°C have a polycrystalline structure. Have obtained Ga2O3 peak (0 1 2) and (2 1 10) and peak silicon (1 1 1) and (4 4 4). The orientation (0 1 2) has the highest intensity and the value of full width half maximum (FWHM) at the smallest substrat temperature 600°C. Transmittance value the smaller the increase in substrate temperature with the largest value of 70% is owned by the substrate temperature of 600 ° C and 60% for a temperature of 635 ° C, with the magnitude of the resulting energy gap is relatively the same, namely 4.60 eV and 4.65 eV.